KELAYAKAN TEKNIS PERENCANAAN ANGKUTAN SEKOLAH DI KOTA PEKANBARU`` - septia gusman (LPPM Universitas Abdurrab, 2021)
In Pekanbaru City, students' trips to and from school tend to use private vehicles, be it motorbikes or those delivered by parents, so the available urban transportation is less attractive. Almost 75% of students use motorbikes, this situation can certainly affect student safety. This can be seen from the number of accidents in 2017 which placed the student profession as a victim in the 2nd position. Therefore, it is necessary to plan safe, comfortable, precise and safe school transportation. This research was conducted at schools in the Lima Puluh District area. The analysis used the method of calculating potential demand, service routes, types and number of fleets. Based on the demand for school transportation, the school bus transportation service area is divided into 6 school transportation routes. The fleet used is medium buses. The operational plan for school transportation is divided into 3 shifts, namely morning, afternoon and evening